Design, engineering and discovery of novel α-helical and β-boomerang antimicrobial peptides against drug resistant bacteria - Bhattacharjya, Surajit (2021)
In an era where the pipeline of new antibiotic development is drying up, the continuous rise of multi-drug resistant (MDR) and extensively drug resistant (XDR) bacteria are genuine threats to human health. Although antimicrobial peptides (AMPs) may serve as promising leads against drug resistant bacteria, only a few AMPs are in advanced clinical trials. The limitations of AMPs, namely their low in vivo activity, toxicity, and poor bioavailability, need to be addressed. Here, we review engineering of frog derived short α-helical AMPs (aurein, temporins) and lipopolysaccharide (LPS) binding designed β-boomerang AMPs for further development. The discovery of novel cell selective AMPs from the human proprotein convertase furin is also discussed.